2009
DOI: 10.1136/jnnp.2009.176982
|View full text |Cite
|
Sign up to set email alerts
|

Progression in prediagnostic Huntington disease

Abstract: Objective To examine rates of decline in individuals at risk for Huntington disease (HD). Methods 106 individuals at risk for HD completed a battery of neurocognitive, psychomotor and oculomotor tasks at two visits, approximately 2.5 years apart. Participants were classified as: (1) without the CAG expansion (normal controls, NC; n=68) or (2) with the CAG expansion (CAG+; n=38). The CAG+ group was further subdivided into those near to (near; n=19) or far from (far; n=19) their estimated age of onset. Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
5
38
0
1
Order By: Relevance
“…This approach can distinguish premanifest individuals from controls by virtue of the former having an increased number of early saccades (responses with unusually short latencies) [2]. Such findings are consistent with other oculomotor studies that have demonstrated the utility of saccadic latency measurement in detecting early changes in HD [1,3,10,11,33].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…This approach can distinguish premanifest individuals from controls by virtue of the former having an increased number of early saccades (responses with unusually short latencies) [2]. Such findings are consistent with other oculomotor studies that have demonstrated the utility of saccadic latency measurement in detecting early changes in HD [1,3,10,11,33].…”
Section: Introductionsupporting
confidence: 60%
“…Hand-tapping parameters differ between HD and control populations and show high reproducibly and correlate with motor Unified Huntington's disease rating scale (UHDRS) changes over time in manifest cases of the disease [28]. However, how hand-tapping rate changes over time in premanifest patients [3,34] is currently unknown, as is whether it can be used to define the transition to manifest disease, as Saft, et al [30] have suggested.…”
Section: Introductionmentioning
confidence: 91%
“…Six of the studies reviewed (see table 1) showed significant changes over time using the Stroop Color Word Test8 10 14–16; the TMT,14–16 or other measures of reaction or movement time,13 14 all of which were found to have substantial effects in the current study. Some have interpreted this finding as reason to emphasise motor and psychomotor measures of HD as superior to other potential assessed outcomes 12.…”
Section: Discussionmentioning
confidence: 51%
“…To this end, we employed three well-established automated methods to analyze structural data obtained from healthy controls and far-from-onset preHD: (1) the VBM Diffeomorphic Anatomic Registration Through Exponentiated Lie Algebra algorithm (DARTEL); (2) the Oxford Centre for Functional MRI of the Brain's (FMRIB's) Integrated Registration and Segmentation Tool (FIRST), and (3) the FreeSurfer software package. We went on to examine the relationship between subcortical and cortical volume with genetic and clinical variables, such as CAG repeat length and the estimated time to motor onset considering the increasing subclinical and neurobiological changes which occur with closer proximity to the motor onset of the disease [5,9,11,17,18]. We finally administered a complementary neuropsychological test battery to relate structural changes to cognitive performance.…”
Section: Introductionmentioning
confidence: 99%